Analysis of Automotive Component Design for Reparation using Additive Manufacturing Technology - Mad Yusoh, Siti Syahara; Abd Wahab, Dzuraidah; Azman, Abdul Hadi (International Journal of Integrated Engineering, 2020)
Remanufacturing is the most value added end-of-life vehicle (ELV) recovery strategy in which parts and components referred to as cores are returned to their next life cycle to as new-condition. Remanufacturing which involved several important steps namely disassembly, cleaning, inspection, repair, reassembly and testing are normally carried out by skilled and experienced workers. Advancement in enabling technologies such as Additive Manufacturing (AM) seemed capable of alleviating limitations in the manual repair and restoration of end-of-life cores. It is foreseen that AM can improve the efficiency of repair and restoration. However, there are several challenges in the restoration process such as limited accessibility to the inner diameter of parts, the presence of grooves, sharp edges and corners, as well as limitations in the types of materials used as filler powder and design that does not facilitate restoration using AM process. To date, there are limited reports on how products should be designed for restoration using AM and also on the capabilities of AM to conduct various kinds of restoration on ELV cores. This paper discusses the potential of AM for restoration based on the analysis of selected automotive components design. The paper concludes with suggestions on the need for design guidelines for AM restoration in view of automating the restoration process for product life cycle extension.